Comparison of Li/Ni antisite defects in Fd-3 m and P4332 nanostructured LiNi0.5Mn1.5O4 electrode for Li-ion batteries. (20th September 2016) - Gu, Yi-Jie; Li, Yu; Chen, Yun-Bo; Liu, Hong-Quan
Highlights: Nano LiNi0.5 Mn1.5 O4 was synthesized through carbonate precipitation method. Li/Ni antisite defects exist in ordered as well as disordered LiNi0.5 Mn1.5 O4 . Disordered LiNi0.5 Mn1.5 O4 has a faster phase transition during discharge process. Abstract: Nanostructured LiNi0.5 Mn1.5 O4 with two different space groups (P43 32 and Fd-3m) were synthesized respectively, by using ammonia-mediated carbonate precipitation. X-ray diffraction and Rietveld refinement revealed that Li/Ni antisite defects exist in ordered as well as disordered LiNi0.5 Mn1.5 O4 cathode materials. Although the degree of Li/Ni antisite defects in Fd–3 m space group was larger compared with that in P43 32 space group, it showed better electrochemical performance. Electrochemical impedance spectroscopy confirmed that the LiNi0.5 Mn1.5 O4 with an Fd–3 m space group has lower charge transfer resistance. Combined with differential curves, we further revealed that there is a faster phase transition during the Li + intercalation process in the LiNi0.5 Mn1.5 O4 with an Fd–3 m space group than in the LiNi0.5 Mn1.5 O4 with a P43 32 space group.